IMPROVING CASH AVAILABILITY OF ATM USING LEAN REPLENISHMENT PULL FOR SHARIA BANK IN INDONESIA - Tazkiyah Herdi; Ardiansyah Dores (Universitas muhammadiyah malang, 2020)
To maintain the company's sustainability of quality and the increasingly rapid competition between banking institutions, a bank must continue to protect its customers from the ease and availability of services when needed anytime and anywhere. Automated Teller Machines (ATM) are the most common banking products and services used by the public. Previously, Activities carried out by the teller can already be done through an ATM. Availability of the ATM has been a special attention among the banking industry and CIT (Cash in transit) company. Factors that cause ATM unavailable are: hardware, receipt, network, and cash, one of the most critical factors is cash availability. Previous study shows some concern of cost and risk of inventory cash on ATM, that leads to study of cash prediction method to replenishment cash of the ATM. Current conditions, Bank ATMs have an average percentage of cash availability in the last 6 months of 92.86%, which means there is 7.1% of cash not available. The aim of this study is to adapt the lean replenishment pull system to manage cash replenishment of the bank ATMs and to achieve level 4 of sigma (99.38%) on ATM cash availability. By collecting, measuring and analyzing availability data and transactions data on both on-site and off-site ATMs samples for the certain period. The proposed model is to determine warning to do the cash replenishment and the Kmin of cash status. Thus, the cash supply at the ATM machine is sufficient, and no idle money occurs.